2009
DOI: 10.1073/pnas.0908812106
|View full text |Cite
|
Sign up to set email alerts
|

A single plant resistance gene promoter engineered to recognize multiple TAL effectors from disparate pathogens

Abstract: Plant pathogenic bacteria of the genus Xanthomonas inject transcription-activator like (TAL) effector proteins that manipulate the hosts' transcriptome to promote disease. However, in some cases plants take advantage of this mechanism to trigger defense responses. For example, transcription of the pepper Bs3 and rice Xa27 resistance (R) genes are specifically activated by the respective TAL effectors AvrBs3 from Xanthomonas campestris pv. vesicatoria (Xcv), and AvrXa27 from X. oryzae pv. oryzae (Xoo). Recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
129
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(133 citation statements)
references
References 33 publications
1
129
0
3
Order By: Relevance
“…By combining the natural EBEs of multiple TAL effectors from three distinct R genes or adding artificial EBEs of corresponding TAL effectors into one complex R gene promoter, the engineered R gene was induced by these effectors and conferred broader spectrum disease resistance (46,47). Although no major R genes have yet been described in citrus, the well-characterized avr gene AvrGf1 may reflect the presence of a potential R gene in grapefruit and sweet orange (3).…”
Section: Discussionmentioning
confidence: 99%
“…By combining the natural EBEs of multiple TAL effectors from three distinct R genes or adding artificial EBEs of corresponding TAL effectors into one complex R gene promoter, the engineered R gene was induced by these effectors and conferred broader spectrum disease resistance (46,47). Although no major R genes have yet been described in citrus, the well-characterized avr gene AvrGf1 may reflect the presence of a potential R gene in grapefruit and sweet orange (3).…”
Section: Discussionmentioning
confidence: 99%
“…TALEs can be applied to transcription control as demonstrated in plants (Boch et al , 2009 ;Romer et al , 2009aRomer et al , ,b , 2010Morbitzer et al , 2010 ;Mahfouz et al , 2011 ;Weber et al , 2011 ; and in mammalian cell cultures (Geissler et al , 2011 ;Miller et al , 2011 ;Zhang et al , 2011 ;Bultmann et al , 2012 ). For engineered transcriptional control, TALE binding sites should be chosen in a way that will minimize off-target effects.…”
Section: Applications Of Tale Proteinsmentioning
confidence: 99%
“…Recently, it was shown that different TAL-boxes can be combined into one promoter to render this promoter responsive to several TAL effectors. 12 This demonstrated that the repeat number influences DNA binding. TAL effectors with a low number of repeats have less protein-DNA interactions than TAL effectors with many repeats and should thus have lower DNA affinity.…”
mentioning
confidence: 95%
“…1A), 4 but does not efficiently recognize DNA sequences with two additional TAL-boxes can be inserted at different positions into a promoter and promoters can be generated that are induced by several TAL effectors. 12 This might be useful to generate plants carrying resistance genes under control of such promoters. These plants will be resistant to infection of bacteria carrying either one of the corresponding TAL effectors.…”
mentioning
confidence: 99%